Oxidative Stress Boosts the Uptake of Cerium Oxide Nanoparticles by Changing Brain Endothelium Microvilli Pattern - Roberta Dal Magro; Agostina Vitali; Stefano Fagioli; Alberto Casu; Andrea Falqui; Beatrice Formicola; Lorenzo Taiarol; Valeria Cassina; Claudia Adriana Marrano; Francesco Mantegazza; Umberto Anselmi-Tamburini; Patrizia Sommi; et al. (MDPI AG, 2021)
Vascular oxidative stress is considered a worsening factor in the progression of Alzheimer's disease (AD). Increased reactive oxygen species (ROS) levels promote the accumulation of amyloid-β peptide (Aβ), one of the main hallmarks of AD. In turn, Aβ is a potent inducer of oxidative stress. In early stages of AD, the concomitant action of oxidative stress and Aβ on brain capillary endothelial cells was observed to compromise the blood-brain barrier functionality. In this context, antioxidant compounds might provide therapeutic benefits. To this aim, we investigated the antioxidant activity of cerium oxide nanoparticles (CNP) in human cerebral microvascular endothelial cells (hCMEC/D3) exposed to Aβ oligomers. Treatment with CNP (13.9 ± 0.7 nm in diameter) restored basal ROS levels in hCMEC/D3 cells, both after acute or prolonged exposure to Aβ. Moreover, we found that the extent of CNP uptake by hCMEC/D3 was +43% higher in the presence of Aβ. Scanning electron microscopy and western blot analysis suggested that changes in microvilli structures on the cell surface, under pro-oxidant stimuli (Aβ or H2O2), might be involved in the enhancement of CNP uptake. This finding opens the possibility to exploit the modulation of endothelial microvilli pattern to improve the uptake of anti-oxidant particles designed to counteract ROS-mediated cerebrovascular dysfunctions.